PERILAKU CREEP BALOK LAMINATED VEENER LUMBER KAYU SENGON (Paraserianthes falcataria) DENGAN TUMPUAN KANTILEVER - , ROBBII ADRIANSYAH KULLIT ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Wood behavior whether it is solid wood or LVL is strongly influenced by time, one of which is creep behaviour. This behavior is a long term behavior that can lead to excessive deflection from the initial design long after the building was erected. The creep behavior of Sengon LVL beam with cantilever support research was conducted by applying 30%, 40%, and 50% loading with controlled and uncontrolled temperature condition in two weeks. Stress levels are determined from fracture load from timber Modulus of Rupture test. In the first test the obtained creep factor to the stress level of 30%, 40%, and 50% are 0,27